Catatan Faktor-faktor yang Mempengaruhi Pelaksanaan Supervisi Klinik oleh Manajer Perawat di Rumah Sakit - Warih Trimulyanto; Megah Andriany; Untung Sujianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine Factors That Influence The Implementation Of Clinical Supervision By Nurse Managers In Hospitals. The method used is a scoping review through a review of relevant articles on topics from Google Scholar, Pubmed, Proquest and Scient Direct with the year of publication 2020 to 2023 with the keywords